CAN PULMONARY SURFACTANT PROTEINS BE RELIABLE INDICATORS OF COVID-19-ASSOCIATED PULMONARY INJURY? - Yuliya Fedorchenko; Olena Zimba (Central Asian Journal of Medical Hypotheses and Ethics, 2022)
The COVID-19 pandemic is still raging all over the world. New variants of the coronavirus emerge and infect recovered from previous infections, vaccinated, and unvaccinated subjects. One aspect remains unchanged that is the lungs are the main targets of the pandemic coronavirus. This challenging situation requires the search for reliable predictive markers of severe and complicated course of the disease. Serum surfactant proteins are known to correlate with pulmonary injury severity in numerous diseases. Measurement of such protein levels may help timely predict the risk. Surfactant proteins can also be helpful diagnostic purposes in COVID-19.